Primary elements: typological innovation and urban performance - Haynes, Nicholas (2024)
This doctorate explicates the dynamic relationship between architecture and the city. Drawing upon Aldo Rossi’s theories, it argues that architectural artifacts and Study Areas—urban areas with identifiable characteristics—are mutually interdependent in the ongoing transformation of the city. Taking as its subject the central island of Berlin—the ‘Spreeinsel’—it first identifies, then explains typological innovations that have caused urban transformations to the ‘Hauptstadt’. It accordingly presents a genealogy of the city’s present-day condition, examining the trajectory of the Study Area from the enclave of royal residence in the 1800s to its current iteration as Berlin’s cultural heart. In the intermediary, it assesses Schinkel’s transformation of the island through the opening of the Altes Museum and his other associated cityscape improvements; the GDR’s post-war reorientation of the islands’ central void spaces towards the east; and the present-day resurrection of the former Berliner Schloß and the implementation of the Museumsinsel Masterplan, each as key moments of alteration. The thesis focuses on the immanent potential of architecture itself, held autonomously by its conventions, objects, and concepts (collectively, that which comprises its 'material'), advocating that architecture’s spatiality has its own reasoning propagated by typology, which operates irrespectively of dialectics beyond its disciplinary frontiers. A logic is developed based on Primary Elements—key urban artifacts which interact with the city’s development in a permanent way—and their instrumentality in propagating change in the city. Typology’s exploitation of persistence is inherently linked to structuring the urban condition, and architecture therefore is considered to have an effect across time, and an area much wider than its immediate envelope. Accordingly, the focus shifts from theory to practice: from what architecture means, to what architecture does; its consequences, effects, and an examination of its potential for transformation. Reasoning fundamental instances of urban alteration, exonerates this research from mere historiographical account—that is, an investigation of period or style, or expression of society’s needs through time. Instead, it is an analysis that foregrounds typology as architecture’s ultimate process of reasoning and its under-explored role in the evolution of the city. Type’s agency is reasoned to be held in the characteristics of relations between Study Area and architecture, rather than the architectural object itself, constituting the agent of change and the locus of innovation.